118 DIFFERENTIAL EXPRESSION OF BONE MORPHOGENETIC PROTEIN-5, PROMYELOCYTIC LEUKEMIA ZINC FINGER AND MEMBERS OF THE GATA FAMILY IN GONADOTROPINOMAS. (1st January 2005) - Li, H. Y.; McDermott, D. S.; Lotts, M. M.; Ertel, J. R.; Xu, M.; Lillehei, K. O.; DeMasters, B. K.; Nielsen-Preiss, S. M.; Pawlowski, J. E.; Wierman, M. E.
Abstract : Gonadotropinomas, which produce α, LHβ, and/or FSHβ subunits, represent 35% of pituitary tumors. They pose a diagnostic challenge, presenting predominantly in men with headaches, decreased libido and impotence. Little is known of their pathogenesis, and identification of tumor-specific genes may help elucidate the molecular mechanisms that are involved. We used the Affymetrix GeneChip Human Genome U133 Plus 2.0 Array to compare gene expression profiles in five gonadotropinomas with six pituitaries obtained from autopsies. Analysis with the Affymetrix GeneChip Operating System showed that 1549 of 39, 000 genes examined were differentially expressed. We then used RT-PCR to analyze further several genes, which have been implicated in proliferation, that had unique expression patterns in our array. Bone morphogenetic proteins (BMPs) are growth factors involved in many aspects of tissue development and morphogenesis. Recently, members of the BMP family have been implicated in the production of FSH by gonadotropes and have been detected in gonadotropinomas. In contrast to prior literature, our microarray analysis showed that BMP-5 was selectively overexpressed 4.8-fold in gonadotropinomas compared with normal pituitary, which was confirmed by semi-quantitative RT-PCR. Thus, BMP-5 may have a previously undescribed role in FSH production and/or in gonadotrope proliferation. The promyelocytic leukemia zinc finger (PLZF) protein belongs to the POZ/zinc-finger family of transcription factors and acts as a negative regulator for GATA-2. GATA-2 and GATA-3 are found in pituitary cell lines and can regulate α-subunit gene expression, and GATA-2 has been detected in pituitary tumors. In our study, PLZF was underexpressed 13.9-fold in gonadotropinomas compared with normals, whereas GATA-2 and GATA-3 were overexpressed 6.7-fold and 26.5-fold, respectively. These data suggest that loss of the transcriptional repressor PLZF, together with activation of GATA family members, may be involved in the development of gonadotropinomas. Thus, various growth and transcription factors are differentially expressed in gonadotropinomas. The evaluation of candidate genes that emerge from these experiments provides a rational approach to investigate mechanisms underlying pituitary tumorigenesis.